Implantação das técnicas espectroscópicas de Laser FlashFotólise e de fosforescência para estudos fotofísicos de sistemas porfirínicos e suas interações com biomoléculas e nanoestruturas - Ducas, Eli Silveira Alves (2023)
The photophysical characterization allows the assessment of processes following the phenomenon of light absorption, which is of interest for various applications, both in the field of materials chemistry and in photomedicine. This work aimed at the photophysical characterization of potential porphyrinic photosensitizers and their interaction with biomolecular systems and nanostructures. To achieve this, the spectroscopic techniques of Transient Absorption (or Laser Flash-Photolysis) and a Spectrophosphorimeter were implemented, and their usage protocols were established. With these techniques in operation, an alternative method for determining the triplet state formation yield and obtaining the singlet oxygen formation yield was proposed, fundamental properties for the characterization of photosensitizers. It was possible to investigate the interaction of water-soluble porphyrins with bovine serum albumin and verify that this interaction affects the triplet states lifetimes and singlet oxygen yields. These parameters were strongly influenced by the presence of oxygen and the porphyrin's location at the interaction sites in the protein structure. Another study conducted was the interaction of cationic porphyrins with manganese ferrite (FeMn2O4) anionic ferrofluids in which the interaction leads to the suppression of fluorescence and singlet oxygen (1O2) generation of the photosensitizers. Interestingly, this interaction is not predominantly governed by electrostatic interactions but mainly through chemsorptives and physisorptives interactions. Additionally, it was demonstrated that photothermal heating breaks the interaction with the nanostructure, restoring the photophysical properties of the photosensitizer, making this system a multifunctional nanostructure with luminescent and theranostics properties.